Novelties of the Insolvency Regulation - Žukauskaitė, Miglė (Teisė, 2018)
This article provides an overview of the main amendments enshrined in the revised version of Insolvency Regulation and a thorough comparison between the old and the new versions of the above-mentioned legal act. The article covers one by one all five main areas affected by amendments assessing, whether problems of the old version have been resolved.
Keywords: none